Age-related Differences in Immune Reactions to SARS-CoV-2 Spike and Nucleocapsid Antigens - Morhart, Patrick; Kehl, Sven; Schuh, Wolfgang; Hermes, Katharina; Meltendorf, Stefan; Neubert, Antje; Schneider, Michael; Brunner-Weinzierl, Monika; Schneider, Holm; Lingel, Holger (In Vivo, 2023)
Background/Aim: The manifestation and severity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections show a clear correlation to the age of a patient. The younger a person, the less likely the infection results in significant illness. To explore the immunological characteristics behind this phenomenon, we studied the course of SARS-CoV-2 infections in 11 households, including 8 children and 6 infants/neonates of women who got infected with SARS-CoV-2 during pregnancy. Materials and Methods: We investigated the immune responses of peripheral blood mononuclear cells (PBMCs), umbilical cord blood mononuclear cells (UCBCs), and T cells against spike and nucleocapsid antigens of SARS-COV-2 by flow cytometry and cytokine secretion assays. Results: Upon peptide stimulation, UCBC from neonates showed a strongly reduced IFN-γ production, as well as lower levels of IL-5, IL-13, and TNF-α alongside with decreased frequencies of surface CD137/PD-1 co-expressing CD4+ and CD+8 T cells compared with adult PBMCs. The PBMC response of older children instead was characterized by elevated frequencies of IFN-γ+ CD4+ T cells, but significantly lower levels of multiple cytokines (IL-5, IL-6, IL-9, IL-10, IL-17A, and TNF-α) and a marked shift of the CD4+/CD8+ T-cell ratio towards CD8+ T cells in comparison to adults. Conclusion: The increased severity of SARS-CoV-2 infections in adults could result from the strong cytokine production and lower potential to immunomodulate the excessive inflammation, while the limited IFN-γ production of responding T cells in infants/neonates and the additional higher frequencies of CD8+ T cells in older children may provide advantages during the course of a SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2023-01-13
Keywords: children; COVID-19; immune response; inflammation; neonates; pediatric immunology; SARS-CoV-2; spike protein